STRATEGI MENINGKATKAN KEPUTUSAN PEMBELIAN KONSUMEN PADA APLIKASI SHOPEE MELALUI CONTENT MARKETING DAN ONLINE CUSTOMER REVIEW - R Rizaldi; U Usman (Samalewa: Jurnal Riset & Kajian Manajemen, 2025)
This study aims to know the effect of content marketing and online customer reviews on consumers buying decisions on the Shopee application (study at Samawa University students). The type of this study was associative study. The types of data used were quantitative and qualitative data, then the source of data sources in this study were primary and secondary data. The populations in this study were active students of Samawa University in 2024 whom used the Shopee application. The numbers of samples in this study were 100 respondents obtained using the Paul-Leedy formula. The tool used to collect data were questionnaires distributed via Google Form. The techniques of data analysis were multiple linear regression, t-test and f-test which were processed using the IBM SPSS 25 program. The results of the study showed that content marketing and online customer reviews had a positive and significant effect on consumer purchasing decisions through the Shopee application, both partially and simultaneously. The coefficient of determination (R2) value was 0.738, which means that the percentage of effect of content marketing and online customer reviews on consumer purchasing decisions through the Shopee application was 73.8%, while the remaining of 26.2% was effected by other factors outside this research, such as ease of use of the application, ease of payment system, convenience of service, convenience in terms of time and practicality, product quality, pay later and installment facilities, trust, and others.